2014
DOI: 10.1038/ncomms6429
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiling of peptides from RNAs classified as noncoding

Abstract: Only a small fraction of the mammalian genome codes for messenger RNAs destined to be translated into proteins, and it is generally assumed that a large portion of transcribed sequences - including introns and several classes of non-coding RNAs (ncRNAs) do not give rise to peptide products. A systematic examination of translation and physiological regulation of ncRNAs has not been conducted. Here, we use computational methods to identify the products of non-canonical translation in mouse neurons by analyzing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 30 publications
5
75
0
Order By: Relevance
“…Peptide sequencing data revealed presence of 250 novel mouse peptides encoded by presumed lncRNAs [113]. The full extent of the novel mammalian proteome encoded by lncRNAs is not yet clear however.…”
Section: Criteria and Features Of Existing Classes And Categories Of mentioning
confidence: 99%
“…Peptide sequencing data revealed presence of 250 novel mouse peptides encoded by presumed lncRNAs [113]. The full extent of the novel mammalian proteome encoded by lncRNAs is not yet clear however.…”
Section: Criteria and Features Of Existing Classes And Categories Of mentioning
confidence: 99%
“… Prabakaran et al [78] reported 250 novel peptides coming from unannotated regions, but only 25 of those mapped to regions outside the boundaries of protein-coding genes, and only three of those had support from Ribo-seq data. When we mapped the 250 peptides from this study against a collection of lncRNAs defined by PLAR [14] and passing stringent filters, we found only two matches, and both mapped to probable pseudogenes.…”
Section: Mass Spectrometry For Detection Of Peptides From Novel Genesmentioning
confidence: 95%
“…Accordingly, recent studies have proposed improved MS methods, including a peptidomics approach [47,75], combined fractional diagonal chromatography (COFRADIC) [72,74,76,77], and other improvements [67,73]; constructed potential peptide databases using RNA-seq or Ribo-seq-based transcriptome reconstructions [47,67,72,78]; and combined multiple MS experiments to increase proteome coverage depth [23,68].…”
Section: Mass Spectrometry For Detection Of Peptides From Novel Genesmentioning
confidence: 99%
“…The most direct evidence for the presence of peptides in planta can be obtained from mass spectrometry analyses. The latter allowed successful detection of several sPEPs in other higher eukaryotes, but many of these were noncanonical sPEPs (Slavoff et al, 2013;Prabakaran et al, 2014). Moreover, since sPEPs often occur at low abundance (Hanada et al, 2013;Andrews and Rothnagel, 2014) and classical proteomic analyses involving data-dependent acquisition mass spectrometry have a bias for highly abundant peptides, they have limited potential to detect sPEPs.…”
Section: Peptides Encoded By Sorfs In Primary Transcripts Of Mirnasmentioning
confidence: 99%